Certain Qualitative Changes In Mastitic Cow Milk - Ramesh, P.; Kumari, K.Nalini; Rao, V.Vaikunta; Reddy, V.Padmanabha; Adilaxmamma , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Mastitis affected milk had a significantly decreased protein, a non-significantly decreased fat and a significantly increased pH (6.7±0.05) and decreased significantly following therapy in both the treated groups. Mean milk protein and fat levels did not vary significantly before and after therapy.